Sistem Tumpang Sari Perkebunan Karet Dalam Rangka Meningkatkan Penghasilan Penyadap Karet di Kecamatan Tanta Kabupaten Tabalong - Lara Andreiany; Rizali (PPJP ULM, 2020)
This study aimed to determine the management patterns of monoculture andintercropping rubber plants and find out which rubber plantation system was moreprofitable in Tanta District, Tabalong Regency. The study's scope was conducted in theTanta Sub-district of Tabalong Regency, and the type of research was quantitativedescriptive. Source of data in the form of primary data obtained from interviewsconducted and processed using profit analysis techniques, revenue, production costs,and Revenue Cost Ratio (R / C).The results of the study showed that rubber plantations with intercroppingpatterns received higher and more profitable revenue compared to monoculture patternrubber plantations.